Free Verse – Theory and Method - Eva Lilja (Annales Universitatis Paedagogicae Cracoviensis. Studia Poetica)
A tension between cognitive factors and cultural conventions constitutes poetic rhythm. Rhythm is formed when reading adjusts the sounds of a poem, and versification means repetitions, caesuras, tactus, prolongations, and so on. This paper presents some prerequisites for investigating free verse using the theory of cognitive versification. Free verse has emerged from the most prestigious historical patterns possible – Greek poetry, the Bible, and the Edda songs. Aesthetic rhythm can be classified according to three principles: serial, sequential, and dynamic rhythm, which are the three basic sets of gestalt qualities. Poetic rhythm uses three time levels that coincide with body rhythms – half a second (a tactus, the pulse), about three seconds (a line, short-term memory), and more than three seconds (semantic coherence, long-term memory). Lineation covers the short-term memory interval and promotes a digital reading that simultaneously keeps one line’s overall meaning in mind. It might explain some of the poetry’s magic. We demonstrate how free rhythms work in a poem by Lawrence Ferlinghetti.